1990
DOI: 10.1210/endo-126-2-687
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Fragmentation of Free and Combined Forms of the β-Subunit of Human Chorionic Gonadotropin*

Abstract: In an attempt to further study various fragments of free and combined forms of hCG beta present in biological fluids, we performed one- and two-dimensional sodium dodecyl sulfate-polyacrylamide gel electrophoresis, followed by Western immunoblotting using antipeptide antibodies directed to the hCG beta-(111-116) portion (monoclonal antibody FB12) antiserum to the hCG beta(8-16) portion or antiserum which was specific for fragments ending at residue 47. Results observed in a crude preparation of urinary hCG dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…The authors concluded that 'invisible LH' was due to the existence of a fragmented form of LH where at least part of the 0 subunit was lost (Pettersson et al, 1992). Since similar observations were made with HCG leading to the discovery of nicked /3 HCG (Puisieux et al, 1990;Bischof et al, 1994), we postulate that the fragmented forms of LH could be nicked /3 LH.…”
Section: Discussionsupporting
confidence: 58%
“…The authors concluded that 'invisible LH' was due to the existence of a fragmented form of LH where at least part of the 0 subunit was lost (Pettersson et al, 1992). Since similar observations were made with HCG leading to the discovery of nicked /3 HCG (Puisieux et al, 1990;Bischof et al, 1994), we postulate that the fragmented forms of LH could be nicked /3 LH.…”
Section: Discussionsupporting
confidence: 58%
“…About a decade ago, we collaborated with the laboratory of Dr. Laurence Cole in an attempt to produce antibodies to 'nicked hCG' (hCGn) which is an isoform of hCG commonly observed in the urine and sometimes in the blood of patients with hCG-secreting tumors and other disorders [25][26][27][28][29][30] . hCGn is a proteolytically damaged form of hCG which has peptide bond cleavages in its ␤ -subunit between residues 43 and 49 [23,25,27,[29][30][31] .…”
Section: Development Of Antibody B152 Which Defi Nes These Isoformsmentioning
confidence: 99%
“…hCGn is a proteolytically damaged form of hCG which has peptide bond cleavages in its ␤ -subunit between residues 43 and 49 [23,25,27,[29][30][31] . Figure 1 shows linear drawings of hCG ␤ which is the immunological focus of this review.…”
Section: Development Of Antibody B152 Which Defi Nes These Isoformsmentioning
confidence: 99%
“…Our observation of the appearance of hCG cf in the urine of four female subjects, after receiving a dose of r-hCG, supports the view that it is derived from the metabolic processing of hCG. Previous studies of pregnant subjects have shown that hCG cf concentrations are 2-10 times that of the hCG dimer, on a molar basis, in pregnancy urine , Blithe et al 1988, Krichevsky et al 1988, Wehmann et al 1989, 1990, de Medeiros et al 1992b. However, in this study, the hCG cf measured was only 12·2% of the amount of hCG excreted in urine, suggesting that, in pregnancy, there may be more than one pathway responsible for the production of hCG cf.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to a wide range of heterogeneous forms of intact hCG, the urine of pregnant females contains free and free subunits, nicked hCG (missing linkages in the 41-54 region) (Puisieux et al 1990 and C-terminal forms, i.e. fragments of the chain (Amr et al 1983) and hCG cf (Kato & Braunstein 1988.…”
Section: Introductionmentioning
confidence: 99%